1983
DOI: 10.1073/pnas.80.15.4827
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of synthetic oligonucleotide insertion mutants for the study of homologous recombination in mammalian cells.

Abstract: Thymidine kinase-deficient mouse L cells have been transformed with plasmid DNAs carrying 8-base-pair Xho I linker insertion mutations in the coding region of the herpes simplex virus type 1 thymidine kinase gene. When the mutant plasmids are introduced individually into LTK-cells, transformation efficiencies are greatly reduced relative to the wild type. However, when two mutant plasmids are cotransferred into the same LTK-recipients, significantly higher frequencies of transformation are observed (30-300 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
41
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 20 publications
4
41
0
Order By: Relevance
“…Substantial evidence obtained by the use of viral and plasmid DNA molecules introduced into mammalian cells indicates that homologous recombination between input molecules occurs at a high frequency (3,4,14,15,(19)(20)(21). Based on these original observations, we developed two related systems which permit a dissection of the recombinational process in mammalian cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence obtained by the use of viral and plasmid DNA molecules introduced into mammalian cells indicates that homologous recombination between input molecules occurs at a high frequency (3,4,14,15,(19)(20)(21). Based on these original observations, we developed two related systems which permit a dissection of the recombinational process in mammalian cells.…”
mentioning
confidence: 99%
“…At 4 h, the precipitate was removed, and the cells were treated with 20% dimethyl sulfoxide for 2 min. The cells were transferred to 400 ,ug of G418 per ml on the following day, and resistant colonies were scored after 14 days.…”
mentioning
confidence: 99%
“…One of the intermediates would be the favored substrate in our original 5'-3' degradative model and the other would be the favored substrate in the alternative 3'--5' degradative model. Our results indicate that the intermediate favored by the 3'--5' model is 10 to 20 times more efficient in generating recombinant tk genes than is the other intermediate.DNA introduced into cultured mammalian cells, either as a calcium phosphate precipitate or by direct microinjection into nuclei, is capable of undergoing efficient homologous recombination before it becomes integrated into chromosomes (11,13,18,22,28,32,34,35,41,42). Frequencies of homologous recombination in the range of 10 to 20% are common in these sorts of experiments (22).…”
mentioning
confidence: 99%
“…We have previously shown that in L cells, the joining of dissimilar DNAs follows a precise scheme (1). DNA-mediated gene transfer can also be used to study homologous recombination between cotransferred DNA fragments of selectable genes (5,14,18,21,25,29,32,35,38).The technique of altering the structure of donor molecules to study recombination has been successfully used in bacteria and fungi (6,7,9,15,17,22,23,34,40). To study homologous recombination in mammalian cells, we constructed a family of plasmids with insertions and deletions in the coding region of the herpes simplex virus type 1 thymidine kinase gene (tk).…”
mentioning
confidence: 99%
“…We have previously shown that in L cells, the joining of dissimilar DNAs follows a precise scheme (1). DNA-mediated gene transfer can also be used to study homologous recombination between cotransferred DNA fragments of selectable genes (5,14,18,21,25,29,32,35,38).…”
mentioning
confidence: 99%